Catalase‐Based Therapeutics: An Antioxidant Enzyme Therapeutic for COVID‐19 (Adv. Mater. 43/2020). Issue 43 (26th October 2020) - Qin, Meng; Cao, Zheng; Wen, Jing; Yu, Qingsong; Liu, Chaoyong; Wang, Fang; Zhang, Jianjun; Yang, Fengmei; Li, Yanyan; Fishbein, Gregory; Yan, Sen; Xu, Bin; et al.
Abstract : In article number 2004901, Jianfeng Chen, Zhihua Gan, Zhanlong He, Yunfeng Lu, and co‐workers report an antioxidant enzyme therapeutic for COVID‐19. They demonstrate that catalase, a naturally occurring enzyme commonly used worldwide in food production and as a dietary supplement, can effectively suppress the replication of coronavirus, regulate production of cytokines, and protect lung tissues from oxidative injury.